Thermally decomposed Ni-Fe-hydrotalcite: a highly active catalyst for the solvent-free N-acylation of different amines by acid chlorides - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
A composite Ni-Fe catalyst obtained from the thermal decomposition of Ni-Fe-hydrotalcite at 600 degrees C shows very high activity in the solvent-free N-acylation of amines by different acid chlorides with high product yields under very mild reaction conditions (viz, room temperature, short reaction period and small amount of catalyst). The catalyst also shows excellent reusability in the reaction. The crystalline phases present in the catalyst are mixed oxides and hydroxides of nickel and iron. The high catalytic activity of the decomposed Ni-Fe-hydrotalcite is attributed to the formation of uniformly distributed Ni-Fe metal oxides and hydroxides. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid chlorides; amines; Decomposition of Ni-Fe-hydrotalcite; N-acylation of amines; Ni-Fe-hydrotalcite derived catalyst

Thermally decomposed Cu-Fe-hydrotalcite. a novel highly active catalyst for o-arylation of naphthol and phenols by aryl halides - Choudhary, Vasant R.; Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar (Catalysis Communications, 2012)
A novel, efficient and environmentally benign method has been reported for the synthesis of diaryl ethers by the o-arylation of napthol or phenols with aryl halides in dimethylformamide (as a solvent) under reflux, using a novel heterogeneous catalyst (having redox properties), obtained from thermal decomposition of Cu-Fe at 600 degrees C in the absence of externally added base. The catalyst comprises Cu(II) and Fe(III) species (oxides and hydroxides), which are uniformly distributed during the catalyst formation. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Aryl halides; C-O cross coupling reaction; Cu-Fe-hydrotalcite; Naphthol; o-Arylation; Phenols